“One's life becomes even more miserable when we hear all those hurtful words”. A mixed methods systematic review of disrespect and abuse in abortion care - Meghana Munnangi; Meghana Munnangi; Priya Shreedhar; Regina Gilyan; Hedda Lippus; Hedda Lippus; Dabney P. Evans; Lauren Maxwell; Lauren Maxwell (Frontiers in Reproductive Health)
BackgroundDisrespect and abuse during facility-based abortion and postabortion care (PAC) manifests in various forms, including disrespect, abuse (physical, verbal, and sexual), stigma, discrimination, failure to meet standards of care, neglect, breaches in privacy and confidentiality, misinformation or a lack of information, mistreatment or undignified care, and the presence of protestors. The objective of this mixed methods systematic review was to describe the various forms of disrespect and abuse that women face based on their personal experiences during facility-based abortion care or PAC.MethodsWe conducted a comprehensive literature search in Embase, Medline, and PubMed using Medical Subject Headings (MeSH) and text-based terms targeting disrespect and abuse in facility-based abortion care. The initial search was conducted in 2019, followed by an updated search in 2023. Thirty-eight studies conducted in 20 countries met the inclusion criteria and were included in this review.ResultsThe most frequently observed form of disrespect and abuse, identified in 33 studies, was the failure to meet care standards in providing quality abortion care or PAC, particularly in terms of offering adequate and accurate information to women before, during and after the procedures which was identified in 21 studies. Additionally, stigma was reported in 22 studies, disrespect in 19 studies, discrimination in 10 studies, and verbal, physical and sexual abuse, as well as humiliation and condescension, each in 9 studies. The presence and impact of abortion protestors were also looked at in 8 studies.ConclusionsOur results indicate the need for multi-level strategies to transform healthcare providers' perceptions and attitudes towards women seeking abortion care and other actions at the individual, institutional, and policy levels to provide quality, respectful abortion care and PAC. This systematic measurement of disrespect and abuse in facility-based abortion care and PAC can help understand the distribution of experiences across different groups.